Effect Of Gum Rosin And Ethyl Cellulose On In Vitro Release Of Venlafaxine Hydrochloride From Hydrophilic Matrix Tablets - Doddayya, H (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT Developing oral controlled release tablets for highly water-soluble drugs with constant release rate has always been a challenge to the pharmaceutical technologist. The present work is focused on the effect of gum rosin (GR) and ethyl cellulose (EC) in controlling the release of highly water-soluble drug venlafaxine Hydrochloride from hydrophilic matrices prepared using Hydroxypropyl methylcellulose K100M (HPMC). Tablets were prepared by direct compression method and were evaluated for physicochemical properties, in vitro swelling and release studies. The mechanism of drug release was analyzed using various kinetics models like zero order, first order, Higuchi and Korsmeyer-Peppas equations. Release profiles indicated that, increasing the polymer concentration has drastically retarded the release of venlafaxine hydrochloride. However, even at higher polymer concentration (50% w/w) of HPMC, controlled drug release over a period of 24 hrs could not be obtained. Matrix tablets prepared with combination of hydrophobic polymers namely F6 (50 % w/w HPMC-GR) and F8 (40 % w/w HPMC-EC) gave controlled release of drug over a period of 24 hrs. The mechanism of drug release from all the matrix tablets followed Non-Fickian diffusion as n values lies between 0.4906 to 0.7185 indicating that polymer swelling and relaxation were both involved in the release process. The results of the study revealed that, matrix tablets prepared using HPMC alone could not efficiently control the release of highly water-soluble drug venlafaxine Hcl. The combination of hydrophobic polymers in hydrophilic matrices gave a controlled release over a period of 24hrs.